2020
DOI: 10.1016/j.mri.2020.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of the brain using direction-averaged signal of DWI images

Abstract: Segmentation of brain tissue in diffusion MRI image space has some unique advantages. A novel segmentation method using the direction-averaged diffusion weighted imaging (DWI) signal is proposed. Two images can be obtained from the fitting of the direction-averaged DWI signal as a function of b-value: one with superior contrast between the gray matter and white matter; one with prominent CSF contrast. A pseudo T1 weighted image can be constructed and standard segmentation tools can be applied. The method was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 18 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…Our proposed method performed tissue segmentation prediction directly from the dMRI data and thus could avoid obvious segmentation errors when transferring the anatomical T2w-based "ground truth" segmentation to the dMRI space. In the literature, anatomical-MRI-based segmentation, e.g., the one obtained by SPM, is usually used as the "ground truth" data (Ciritsis et al, 2018;Schnell et al, 2009;Cheng et al, 2020), since the segmentation appears in good agreement with the known anatomy. However, transferring T1w-or T2wbased segmentation into the dMRI space is challenging due to the image distortions in dMRI data, which affected inter-modality registration significantly (Albi et al, 2018;Wu et al, 2008;Jones and Cercignani, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our proposed method performed tissue segmentation prediction directly from the dMRI data and thus could avoid obvious segmentation errors when transferring the anatomical T2w-based "ground truth" segmentation to the dMRI space. In the literature, anatomical-MRI-based segmentation, e.g., the one obtained by SPM, is usually used as the "ground truth" data (Ciritsis et al, 2018;Schnell et al, 2009;Cheng et al, 2020), since the segmentation appears in good agreement with the known anatomy. However, transferring T1w-or T2wbased segmentation into the dMRI space is challenging due to the image distortions in dMRI data, which affected inter-modality registration significantly (Albi et al, 2018;Wu et al, 2008;Jones and Cercignani, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that our proposed method was able to correctly segment in areas where the T2w coregistered segmentation were apparently wrong, thus generating a visually more correct segmentation corresponding to the anatomy as appearing on the T2w image. Similar to previous studies (Beejesh et al, 2019;Hui et al, 2015;Steven et al, 2014;Cheng et al, 2020;Yap et al, 2015), we chose to calculate the accuracy against the "ground truth" segmentation from co-registered anatomical MRI data. Therefore, regions where our method correctly labeled the tissue type but the "ground truth" did not would cause a lower accuracy score.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations